Sustainable Home Design by Applying Control Science - Fujihira, Kazutoshi (IntechOpen, 2017)
Today's homes must prepare for a progressing ageing population and an increasing risk caused by climate change, as well as to reduce CO2 emissions. How homes can be designed to meet all of these requirements? How such design can be promoted in the housing market? Sustainable Home Design by Applying Control Science answers these questions, by using a novel approach. Kazutoshi Fujihira, an innovative environmental scientist and sustainable housing award winner, demonstrates the "control system for promoting sustainable home design" with the "sustainable design guidelines" and "sustainability checklist". Moreover, the chapter of case study illustrates an actually designed and constructed house, which shows excellent sustainability and energy-saving performance.